2017
DOI: 10.15171/jcs.2017.028
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of anxiety in 3-9 year old children receiving nursing intervention

Abstract: Introduction: Nurses are in an ideal position to provide special care for anxious children admitted in hospital wards. Thus, the objectives of the study were to identify the common nursing procedures done for children and to measure their level of anxiety. Methods: A cross-sectional descriptive study was conducted at a district hospital in Philippines. The respondents of the study were 235 children aged 3 – 9 years old admitted in the pediatric ward. The descriptive characteristics of the children were record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…It has been suggested that the most comprehensive assessment of anxiety should involve the use of a combination of behavioral, physiological, and self-report measurement techniques. 1 A self-report measure employing pictures would serve better to young children. Hence, the present investigation employed a combination of psychometric test and biological markers for the assessment of anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the most comprehensive assessment of anxiety should involve the use of a combination of behavioral, physiological, and self-report measurement techniques. 1 A self-report measure employing pictures would serve better to young children. Hence, the present investigation employed a combination of psychometric test and biological markers for the assessment of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Further, there is evidence to infer that children are more anxious than adults when they receive medical treatment and care. 1 Anxiety is defined as a nonspecific feeling of apprehension, worry, uneasiness, or dread, the source of which may be vague or unknown. Dental anxiety has been defined as "abnormal fear or dread of visiting the dentist for preventive care or therapy and unwarranted anxiety over dental procedures."…”
Section: Introductionmentioning
confidence: 99%
“…The VPT is a validated measure of state anxiety in pediatric patients aged .2 years. [13][14][15] The test consists of a series of 8 cards, each consisting of 2 child figures, 1 "anxious" and 1 "nonanxious." Subjects were shown the cards in a predetermined numerical order and asked to point to the figure that they felt like most at the time.…”
Section: Vptmentioning
confidence: 99%
“…The in research that children who have had previous experiences of being treated have a greater level of anxiety and fear than children who have never been treated before. 18,19 Analysis of the care class with the fear score after the intervention obtained P value>0.05 so that there was no difference in the relationship between treatment class and the decrease in the hospitalization fear score. In grade 2 or grade 3 the child care room consists of 3-4 patients in one room so that the child's needs for socialization can still be met.…”
Section: Groupmentioning
confidence: 98%